(untitled) (Hoboken, NJ, 2005)
This publication provides an in-depth interpretation of UPC language specifications for use in highly parallel systems. With its extensive use of examples, UPC programming case studies, and illustrations, it offers new insights into developing efficient and effective UPC applications such as high-speed signal processing and pattern recognition. As an added feature, readers have access to an ftp site containing an electronic copy of the full code and can make files for all the examples given in the text.
Keywords: Parallel programming (Computer science),Ngôn ngữ lập trình máy tính,Lập trình song song (Khoa học máy tính),UPC (Computer program language)